Expressive Writing as a Therapeutic Process for Drug-Dependent Women. Issue 1 (January 2014) - Meshberg-Cohen, Sarah; Svikis, Dace; McMahon, Thomas J.
Background: Although women with substance use disorders (SUDs) have high rates of trauma and posttraumatic stress, many addiction programs do not offer trauma-specific treatments. One promising intervention is Pennebaker's expressive writing, which involves daily, 20-minute writing sessions to facilitate disclosure of stressful experiences. Methods: Women ( N = 149) in residential treatment completed a randomized clinical trial comparing expressive writing with control writing. Repeated-measures analysis of variance was used to document change in psychological and physical distress from baseline to 2-week and 1-month follow-ups. Analyses also examined immediate levels of negative affect following expressive writing. Results: Expressive writing participants showed greater reductions in posttraumatic symptom severity, depression, and anxiety scores, when compared with control writing participants at the 2-week follow-up. No group differences were found at the 1-month follow-up. Safety data were encouraging: although expressive writing participants showed increased negative affect immediately after each writing session, there were no differences in pre-writing negative affect scores between conditions the following day. By the final writing session, participants were able to write about traumatic/stressful events without having a spike in negative affect. Conclusions: Results suggest that expressive writing may be a brief, safe, low-cost, adjunct to SUD treatment that warrants further study as a strategy for addressing posttraumatic distress in substance-abusing women.